"Slowly, slowly, slowly," said the sloth - Carle, Eric (London Penguin Books, 2005)
Challenged by the other jungle animals for its seemingly lazy ways, a sloth living in a tree explains the many advantages of his slow and peaceful existence.
Keywords: Sloths -- Fiction; Jungle animals -- Fiction; Animals -- Fiction